Relevansi Kepemimpinan Melkisedek yang Berintegritas bagi Pemimpin Gereja Bethel Indonesia di Manokwari - Pieter Tauran; Asep Afaradi (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2026)
Church leadership with integrity is a major challenge today. Melchizedek, a biblical figure of leadership (Genesis 14 and Hebrews 7), serves as a special example because he was both a priest and a king who had no beginning or end. This study aims to determine how Melchizedek's leadership with integrity can be applied by the leaders of the Indonesian Bethel Church in Manokwari. The method used in this research is a qualitative study through reading and reviewing various books and writings. The results indicate that Melchizedek's leadership principles, such as justice, a love of service, and remaining faithful to God, are highly suitable for application in today's church. In conclusion, integrity is crucial in church leadership because it can build trust and create a healthy church community.